Gravity field anomalies in Antarctic Peninsula area based on GOCE satellite gradiometry, marine and aerogravimetry - Marchenko, D. O.; Maksymchuk, V. Yu. (Ukrainian Antarctic Journal, 2013)
Regular 1′ free-air anomalies grid was constructed on the basis of GOCE data, marine and aerogravity data. For this the Gauss-Kolmogorov-Winer algorithm was applied with some modifications. Resulting set shows a connection between the gravity field and tectonic in region.